The Torah as Theological Foundation of Christian Education - Sariyanto; Chandra, Adi (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2021)
The world today is marked by the development of the times, where technology continues to develop rapidly. These conditions can hurt human life, where people begin to leave religious teachings and are not centered on God. So humans can experience a spiritual decline. If the church or Christian educators do not anticipate it, it is feared that Christians will not have the right basic theology. The purpose of writing is to find the theological basis in Christian religious education centered in the Old Testament. This journal was written with a qualitative descriptive method through library research. The conclusion in this paper is: in the Old Testament theological principles in forming the basis of Christian religious education, as well as figures of faith who hold fast to God, are examples of life today. Christian families and educators have a responsibility to teach a Christian faith centered on the truth of God’s word. Christian religious education can be qualified when Christians praise God and become witnesses of Christ during this world.